Cost of introducing and delivering malaria vaccine (RTS,S/AS01E) in areas of seasonal malaria transmission, Mali and Burkina Faso - Jean Bosco Ouédraogo; Alassane Dicko; Ranju Baral; Clint Pecenka; Halimatou Diawara; Fadima Yaya Bocoum; Ann Levin; Cynthia Lee; Fatoumata Koita; Rosemonde Guissou; Seydou Yabré; Seydou Traoré; et al. (BMJ Global Health, 2023)
Background The WHO recommends use of the RTS,S/AS01E (RTS,S) malaria vaccine for young children living in areas of moderate to high Plasmodium falciparum malaria transmission and suggests countries consider seasonal vaccination in areas with highly seasonal malaria. Seasonal vaccination is uncommon and may require adaptations with potential cost consequences. This study prospectively estimates cost of seasonal malaria vaccine delivery in Mali and Burkina Faso.Methods Three scenarios for seasonal vaccine delivery are costed (1) mass campaign only, (2) routine Expanded Programme on Immunisation (EPI) and (3) mixed delivery (mass campaign and routine EPI)), from the government’s perspective. Resource use data are informed by previous new vaccine introductions, supplemented with primary data from a sample of health facilities and administrative units.Findings At an assumed vaccine price of US $5 per dose, the economic cost per dose administered ranges between $7.73 and $8.68 (mass campaign), $7.04 and $7.38 (routine EPI) and $7.26 and $7.93 (mixed delivery). Excluding commodities, the cost ranges between $1.17 and $2.12 (mass campaign), $0.48 and $0.82 (routine EPI) and $0.70 and $1.37 (mixed delivery). The financial non-commodity cost per dose administered ranges between $0.99 and $1.99 (mass campaign), $0.39 and $0.76 (routine EPI) and $0.58 and $1.28 (mixed delivery). Excluding commodity costs, service delivery is the main cost driver under the mass campaign scenario, accounting for 36% to 55% of the financial cost. Service delivery accounts for 2%–8% and 12%–23% of the total financial cost under routine EPI and mixed delivery scenarios, respectively.Conclusion Vaccine delivery using the mass campaign approach is most costly followed by mixed delivery and routine EPI delivery approaches, in both countries. Our cost estimates provide useful insights for decisions regarding delivery approaches, as countries plan the malaria vaccine rollout.